The NAS-NRC Twin Registry and Duke Twins Study of Memory in Aging: An Update. (29th December 2019) - Gatz, Margaret; Plassman, Brenda L.; Tanner, Caroline M.; Goldman, Samuel M.; Swan, Gary E.; Chanti-Ketterl, Marianne; Walters, Ellen E.; Butler, David A.
Abstract: The National Academy of Sciences-National Research Council (NAS-NRC) Twin Registry is one of the oldest, national population-based twin registries in the USA. It comprises 15, 924 White male twin pairs born in the years 1917–1927 ( N = 31.848), both of whom served in the armed forces, chiefly during World War II. This article updates activities in this registry since the most recent report in Twin Research and Human Genetics (Page, 2006 ). Records-based data include information from enlistment charts and Veterans Administration data linkages. There have been three major epidemiologic questionnaires and an education and earnings survey. Separate data collection efforts with the NAS-NRC registry include the National Heart, Lung, and Blood Institute (NHLBI) subsample, the Duke Twins Study of Memory in Aging and a clinically based study of Parkinson's disease. Progress has been made on consolidating the various data holdings of the NAS-NRC Twin Registry. Data that had been available through the National Academy of Sciences are now freely available through National Archive of Computerized Data on Aging (NACDA).